Psychological Interventions for the Management of Glycemic and Psychological Outcomes of Type 2 Diabetes Mellitus in China: A Systematic Review and Meta-Analyses of Randomized Controlled Trials - Chapman, Anna; Liu, Shuo; Merkouris, Stephanie; Enticott, Joanne C.; Yang, Hui; Browning, Colette J.; Thomas, Shane A. (Frontiers in Public Health, 2015)
Introduction China has the largest number of type 2 diabetes mellitus (T2DM) cases globally and T2DM management has become a critical public health issue in China. Individuals with T2DM have an increased risk of developing mental health disorders, psychological disturbances and functional problems associated with living with their condition. Previous systematic reviews have demonstrated that, generally, psychological interventions are effective in the management of T2DM related outcomes; however these reviews have predominantly included studies conducted within English speaking countries, and have not determined the efficacy of the varying types of psychological interventions. As such, this paper aims to synthesize evidence and quantify the efficacy of psychological therapies for the management of glycemic and psychological outcomes of T2DM in China, relative to control conditions. Methods A systematic search (MEDLINE, PsycINFO, CINAHL, Cochrane Central Register of Controlled Trials, CNKI, Wangfang Data) for all years to December 2014 identified all available literature. Eligibility criteria included: Peer reviewed journal articles; RCTs assessing the efficacy of a psychological therapy for the management of T2DM; adults diagnosed with T2DM or non-insulin dependent diabetes mellitus; Chinese speaking participants (in mainland China). Outcome measures were glycated hemoglobin, blood glucose concentration, depression, anxiety and quality of life. Effect sizes were pooled using a random effects model. Negative effect sizes corresponded to positive outcomes favoring the intervention. Results 45 RCTs were eligible for the meta-analyses. Cognitive behavioral therapy (CBT) and motivational interviewing (MI) were more effective than the control condition in the reduction of glycated hemoglobin (CBT: -0·97 [95% CI -1·37 to -0·57]; MI -0·71 [95% CI -1·00 to -0·43]). CBT and client-centered therapy (CCT) were also associated with reductions in depression and blood glucose concentration, and CBT with reductions in anxiety. Conclusion Psychological interventions, namely, CBT, MI and CCT are effective in improving certain T2DM related outcomes in China. Considerable levels of heterogeneity and unclear risk of bias associated with most included RCTs suggest caution when interpreting results. In China, where the burden of T2DM is increasing, psychological interventions may provide promising approaches to assist in the management of T2DM to delay the progression of T2DM related outcomes.